Urban Green Islands and Cardiovascular Health: A Narrative Review with a Case Illustration from Tianjin - Jingyi Jiang (Theoretical and Natural Science, 2026)
High-density urbanization intensifies heat and air pollution, which increases cardiovascular disease (CVD) risk, particularly in aging urban populations. Urban Green Islands (UGIs), including pocket parks, microforests, and small vegetation corridors, have emerged as nature-based solutions with potential cardiovascular benefits. This paper uses a narrative literature review to synthesize peer-reviewed epidemiological, experimental, and satellite-based studies published between 2017 and 2026, and adds a descriptive case illustration from Tianjin, China. The reviewed evidence suggests that UGIs may reduce cardiovascular risk through microclimate cooling, pollutant deposition, stress buffering, and promotion of physical activity. Their benefits appear strongest when they are located within 300-500 m of residences and when they are accessible to socioeconomically disadvantaged communities. The Tianjin case applies a vegetation-to-temperature-to-regression framework to illustrate how greening and thermal exposure jointly relate to district-level CVD incidence. Overall, UGIs appear to be important environmental protective factors that support cardiovascular health, health equity, and urban resilience.